Deposition of NiFeCo Thin Film for Giant Magnetoresistance (GMR) Material by dc-Unbalanced Magnetron Sputtering Method - Togar Saragi; Mitra Djamal; Khairurrijal Khairurrijal; M. Barmawi (Indonesian Journal of Physics, 2003)
Deposition of NiFeCo thin films have been successfully grown by dc-unbalanced magnetron sputtering method. The linearity coefficient of thin films were 0.9169 at horizontal position and 0.953 at vertical position (sample 250902) and 0.8076 at horizontal position and 0.889 at vertical position (sample 260902), which is close to 1 for the ideal R-H characteristic. From XRD characterization, it was shown that the NiFeCo thin films were amorphous, and small grains, which was observed by SEM. The thin films thickness were 0.42 micrometer (sample 250902) and 0.26 micrometer (sample 260902). EDAX characterization shows that the composition of weight percent were: Ni(71.57%):Fe(7.44%):Co(20.99%) for sample 250902 and Ni(72.21%):Fe(10.27%):Co(17.25%) for sample 260902. These preliminary results will be discussed for future possibility of fabrication thin films in the prospect for device applications.